Comparison of Flavonoid Compounds in the Flavedo and Juice of Two Pummelo Cultivars (Citrus grandis L. Osbeck) from Different Cultivation Regions in China - Zhang, Mingxia (Molecules, 2014)
The objective of this study was to investigate the effect of different cultivation regions on the pattern and content of flavonoids in two pummelo cultivars (C. grandis L. Osbeck) in China. Results showed that similar patterns of flavonoids were observed in the flavedo or juice of each pummelo cultivar from these cultivation regions, whereas the individual flavonoid content showed unique characteristics. Naringin, the predominant flavanone glycoside, showed the highest content in both flavedo and juice of C. grandis “Guanximiyu” from the Pinghe of Fujian (FJ) cultivation region compared with the Dapu of Guangdong (GD) and Nanbu of Sichuan (SC) regions. However, its content in the flavedo of C. grandis “Shatianyu” from the Pingle of Guangxi (GX) was significantly lower than in the GD and SC regions. Vicenin-2 appeared to be the dominant flavone C-glycoside in the flavedo of both cultivars, and the lowest content was observed in the flavedo of C. grandis “Guanximiyu” from the SC region. However, C. grandis “Shatianyu” contained the highest content of vicenin-2 in the flavedo from SC region. Similarly, the predominant flavone O-glucoside, rhoifolin, showed the highest content in C. grandis “Guanximiyu” from the GD and FJ regions, whereas C. grandis “Shatianyu” in SC region showed the highest content of rhoifolin. Cluster analysis suggested that genotype played a primary role in determining the flavonoid profiles of pummelo cultivars, whereas regional differences significantly affected the flavonoid distribution of pummelo cultivars potentially via affecting the direction of flavonoid accumulation in pummelo.